Perception of Teachers and Students by Using Interactive Multimedia to Improve Science Literacy and Self-Efficacy - Tri Hastuti Wibowo; Sunyono Sunyono; R B Rudibyani (Universitas Muhammadiyah Purwokerto, 2020)
The purpose of this study is to analyze and explain Perception of Teachers and Students by Using Interactive Multimedia to Improve Science Literacy and Self Efficacy. The research method was descriptive method.The population in this study were ten junior high school teachers and seventy five junior high school students from five different schools. The data collection used questionnaires and data analysis techniques using percentages. The results showed that the teachers perception of learning using interactive multimedia in the aspect of implementation was low category, because teachers still use books and students worksheet. Teachers perceptions of scientific literacy aspects are low, but teachers have tried to apply them in learning. Furthermore, teachers perceptions of students self efficacy in category “medium”. Students' perceptions for aspects of learning using Multimedia interactive (MMI) and scientific literacy were still low, but on aspect of students self efficacy in the “high” category. Then, the percentage of students requirements of using MMI in learning in “high” category. It can be concluded that using MMI to improve students sains literacy and students self efficacy.